How Performance Mediate the Effects of Participation and Control Environment on Transparency - Rahayu, Sri; Yudi, Yudi; Rahayu, Rahayu; Jumaili, Salman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022)DO - 10.24843/JIAB.2022.v17.i01.p05, 2022)
This study examines the effect of participation and the internal environment on transparency with performance as a mediator. PLS 3.0 was used to analyze the research data. We were collecting data using a questionnaire. The research respondents were principals, teachers, and employees of public elementary schools. The number of respondents was as many as three participants. The results showed that participation and control environment had a positive effect on performance. Performance has a positive impact on transparency. Performance can mediate the effect of participation and control environment on transparency. Schools and local governments can use performance measurement with educational scorecards to assess school performance. School performance is evaluated comprehensively, not only from the management of academic activities. Schools must pay attention to financial management performance as well. School transparency must also be considered to increase the trust of all stakeholders. Keywords: educational scorecard, school, stakeholders, academic, finance